Pengaruh Variasi Produk Dan Store Atmosphere Terhadap Repurchase Intention - Saraswati, Kadek Dina; Sanjaya, Putu Krisna Adwitya; Trarintya, Mirah Ayu Putri (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2021)
The purpose of this study was to determine the effect of product variation and store atmosphere on repurchase intention of Outlet Pizza Hut cabang Gatot Subroto in Denpasar. This research was conducted at Outlet Pizza Hut cabang Gatot Subroto in Denpasar with a total sample of 100 peoples. While the data analysis techniques are validity, reliability, classic assumption test, multiple linear regression analysis, determination analysis, t test, and F test. The test results show that there is a positive and significant effect product variation on repurchase intention where values are obtained the t1-count is 5.453, greater than t-table of 1,658 with a sig value of 0.000. There is a positive and significant effect of store atmosphere on repurchase intention the regression coefficient t2-count is 6.703, greater than t-table 1.658 with a sig 0.000. There is a positive and significant effect effect of product variation and store atmosphere on repurchase intention of Outlet Pizza Hut cabang Gatot Subroto in Denpasar. When seen from the results of the F-test obtained F-count is 157.651 greater than the F-table of 3.07 and a sig value of 0,000.